Kuwait government entities e-business continuity and disaster recovery plan - Alenezi, Khalid; Alshaikhli, Imad Fakhri Taha; AlAhmad, Mohammad A. (Design for Scientific Renaissance, 2014)
All organization's target to protect their data and IT infrastructure form any cyber-attack or from hackers breaches, in order to keep Information technology running in the event of threats. This paper proposes Business Continuity Plan serve Kuwait government entities, agreeing to theoretical and statistical studies, in future ensuring the stability of all e-services established in Kuwait as share of the e-Government scheme. This solution will guarantee the steadiness of e-business in Kuwait government entities, and how to implement this plan.